2008
DOI: 10.1080/15435070802107165
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Particle Swarm Optimization and its Application in Location of Biomass Power Plants

Abstract: This work introduces a binary particle swarm optimization based approach to locate the optimal location for biomass-based power plants. The proposed algorithm also offers the supply area for the biomass plant. The optimal location can be addressed as a nonlinear optimization problem. The profitability index is the fitness function for the binary optimization algorithm. It is defined as the ratio between the net present value and the initial investment.The constraints for simulations are: the biomass power plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 22 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Many studies combined traditional optimization methods with heuristic algorithms. Several studies highlighted the reduction of computational costs by using heuristics (Asadi et al, 2018; Kumar et al, 2015; Lopez et al, 2008; López et al, 2008), especially when solving BSC models with a large number of variables and constraints (Asadi et al, 2018). Kumar et al reported that adaptive large neighborhood search (ALNS), a heuristic algorithm, took 140 s while CPLEX took ~3 h to find the solution for the same BSC problem (Kumar et al, 2015).…”
Section: Applications Of Artificial Intelligence To Bioenergy Systemsmentioning
confidence: 99%
“…Many studies combined traditional optimization methods with heuristic algorithms. Several studies highlighted the reduction of computational costs by using heuristics (Asadi et al, 2018; Kumar et al, 2015; Lopez et al, 2008; López et al, 2008), especially when solving BSC models with a large number of variables and constraints (Asadi et al, 2018). Kumar et al reported that adaptive large neighborhood search (ALNS), a heuristic algorithm, took 140 s while CPLEX took ~3 h to find the solution for the same BSC problem (Kumar et al, 2015).…”
Section: Applications Of Artificial Intelligence To Bioenergy Systemsmentioning
confidence: 99%
“…whereas, for the slack bus, the voltage is assumed to be 1∟0. Now that the objective and constraints are defined clearly, the exhaustive search method is used in this paper to get the optimal PP as in [20].…”
Section: Optimization Problemmentioning
confidence: 99%
“…López et al [120] presented a binary PSO-based method to accomplish optimal location of biomass-fuelled systems for distributed power generation with forest residues as biomass source, and the results outperformed those obtained by a GA when maximizing a profitability index taking into account technical constraints. In [121] the authors also applied a PSO algorithm for the optimal location and supply area for biomass-based power plants. There are also a number of researches reported on the application of PSO in the design and control of hybrid photovoltaic systems [122][123][124][125][126].…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%